2019
DOI: 10.14718/revarq.2019.21.2.2597
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort in buildings for wet processing of coffee

Abstract: Thermal comfort in buildings for wet processing of coffee Confort térmico en edificaciones para procesamiento húmedo de café Conforto térmico em instalações para processamento úmido de café

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This could be attributed to the closed lantern window in this treatment, which reduces its natural ventilation area compared to T1, and the limited effectiveness of the chimney effect [43], essential for the transfer of energy and vapor mass. To improve thermal comfort in the oven thermal zone, Studies have shown that reducing exposure duration is one way to protect employees against infrared radiation and high temperatures, wearing specialist clothes, such as aluminized garments, and appropriate eye protection, such as infraredfiltered glasses, can help prevent injuries or lessen their severity [44,45].…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to the closed lantern window in this treatment, which reduces its natural ventilation area compared to T1, and the limited effectiveness of the chimney effect [43], essential for the transfer of energy and vapor mass. To improve thermal comfort in the oven thermal zone, Studies have shown that reducing exposure duration is one way to protect employees against infrared radiation and high temperatures, wearing specialist clothes, such as aluminized garments, and appropriate eye protection, such as infraredfiltered glasses, can help prevent injuries or lessen their severity [44,45].…”
Section: Resultsmentioning
confidence: 99%
“…I n Colombia, coffee is mainly processed wet, through sub-processes that include pulping, fermentation, washing, and drying of the beans. The bioclimatic conditions of the facilities where these processes take place can be decisive for both the comfort of the workers (Guerra-García et al, 2019) and the quality preservation of dry parchment coffee. The coffee is often stored there for a long time (sometimes exceeding two weeks), where a large amount of heat and steam is generated by the machines during mechanical drying (Osorio et al, 2018;Osorio et al, 2020).…”
mentioning
confidence: 99%
“…The WBGT index is an indicator of thermal comfort that considers air temperature, metabolism, radiant heat, air velocity, and relative humidity as the main drivers of thermal overload (MTSS, 1979;ISO 7243, 1982;ABNT-NBR, 2011;Roscani et al 2017). Guerra-García et al (2019) used this index for comfort analysis in coffee post-harvest facilities in Colombia, obtaining satisfactory results.…”
mentioning
confidence: 99%
See 1 more Smart Citation